Pemanfaatan Quizizz Sebagai Alat Evaluasi Berbasis Mapping pada Mahasiswa Pendidikan Ekonomi - Amelia, Nur Amelia; Mardialta, Intan; Putri, Desi Armi Eka (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Quizizz is one of the digital learning platforms that can be used to support the technology-based evaluation process. This article aims to examine the use of Quizizz as a mapping-based evaluation tool in students of the Economics Education study program. The method used is a literature study. The data comes from various scientific articles indexed on the Google Scholar database. Data analysis is carried out qualitatively with the stages of data reduction, data presentation, and conclusion drawing. The findings of this study show that Quizizz is able to improve students' understanding of economic concepts through interactive features such as quizzes and data visualization. The mapping-based evaluation applied through Quizizz helps students to map the relationships between concepts more effectively. In this way, Quizizz not only improves efficiency but also makes the learning process more interesting and enjoyable. This article recommends the use of Quizizz as an alternative evaluation tool that is innovative and suitable for modern educational needs